Evaluation of One Step Nucleic Acid Amplification for detection of lymph node metastases compared to histopathological ultrastaging in women with endometrial cancer: a protocol for a diagnostic accuracy study - Jan Kostun; Alessandra Mescalchin; Martin Pešta; Robert Slunečko; Khaled M. Ismail; Vendula Smoligová; Jiri Presl (BMC Women's Health)
Abstract Background This is a multicentre, European, prospective trial evaluating the diagnostic accuracy of One Step Nucleic Acid Amplification (OSNA) compared to sentinel lymph nodes histopathological ultrastaging in endometrial cancer patients. Methods Centres with expertise in sentinel lymph node mapping in endometrial cancer patients in Europe will be invited to participate in the study. Participating units will be trained on the correct usage of the OSNA RD-210 analyser and nucleic acid amplification reagent kit LYNOAMP CK19 E for rapid detection of metastatic nodal involvement, based on the cytokeratin 19 (CK19) mRNA detection. Endometrial cancer patients ≥ 18 years listed for surgical treatment with sentinel lymph node mapping, with no history of other types of cancer and who provide a valid written consent will be considered potentially eligible for the study. However, they will only be enrolled if a successful sentinel lymph node mapping is retrieved. Each node will be processed according to the study protocol and assessed by both OSNA and ultrastaging. Discussion The accuracy of OSNA (index test) will be assessed against sentinel lymph node histopathological ultrastaging (reference test). This European study has the potential to be the largest study on the use of OSNA in endometrial cancer to date. OSNA could represent a modern diagnostic alternative to sentinel lymph node ultrastaging with the added benefits of standardisation and fast results. Trial registration The study was registered in the German Clinical Trial Register – Nr. DRKS00021520, registration date 25th of May 2020, URL of the trial registry record: https://drks.de/search/en/trial/DRKS00021520 .